Respuesta :
-3(5y + 9) - 7y = 4(y - 4) - 1
-15y - 27 - 7y = 4y - 16 - 1
-15y - 7y - 4y = -16 - 1 + 27
-26y = 10
y = 10 / -26 = -5/13 answer
-15y - 27 - 7y = 4y - 16 - 1
-15y - 7y - 4y = -16 - 1 + 27
-26y = 10
y = 10 / -26 = -5/13 answer
I. (distribute the -3 to the equation inside the parentheses) -15y-27-7y=4(y-4)-1. (-3x5y=-15y, -3x9=-27).
II. (distribute the 4 to the equation inside the parentheses) -15y-27-7y=4y-16-1. (4xy=4y, 4x(-4)=-16).
III. (combine like terms, -15y and -7y, and -16 and -1) -22y-27=4y-17. (-15y-7y=-22y and -16-1=-17).
IV. (isolate the variable, add 27 to both sides) -22y=4y+10. (-17+27=10).
V. (isolate the variable, subtract 4y from both sides) -26y=10. (-22y-4y=-26y).
VI. (isolate the variable, divide 10 by -26 to get y by itself) y=-0.3846.
Hope this helps!
II. (distribute the 4 to the equation inside the parentheses) -15y-27-7y=4y-16-1. (4xy=4y, 4x(-4)=-16).
III. (combine like terms, -15y and -7y, and -16 and -1) -22y-27=4y-17. (-15y-7y=-22y and -16-1=-17).
IV. (isolate the variable, add 27 to both sides) -22y=4y+10. (-17+27=10).
V. (isolate the variable, subtract 4y from both sides) -26y=10. (-22y-4y=-26y).
VI. (isolate the variable, divide 10 by -26 to get y by itself) y=-0.3846.
Hope this helps!